PHYSICAL AND CHEMICAL PRINCIPLES OF ACTION OF REVERSE OSMOSIS MEMBRANE FOULING INHIBITORS AND METHODS OF OPTIMAL USAGE THEREOF - Орестов, Є. О.; Мітченко, Т. Є. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2013)
The article provides an overview of the two major classes of modern inhibitors of reverse osmosis membrane element fouling used in water treatment processes, namely the phosphonate compounds and polymer acrylic acid derivatives with different functional groups. The brief characteristics of different types of fouling — colloidal, organic, inorganic and biofouling are given. Special attention is paid to physical and chemical principles of the formation of crystals of sparingly soluble salts from supersaturated solutions and the deposition of these crystals on the surface of the membrane (the phenomenon of scaling), and the factors that affect the scaling. The main mechanisms of action of inhibitors of various classes — threshold effect, effect of deformation and effect of dispersion are described. Physical and chemical factors that determine the effectiveness of the threshold effect inhibitors are analyzed. A list of the main representatives of phosphonate and polymeric reagents, range and principle of action, advantages and disadvantages of each are given, and main modern commercial antiscalants produced with the use of these reagents are mentioned. The information on the forms and methods of application of modern antiscalant reagents is given with focus on use of different filter materials, primarily ion exchange resins, as carriers of antiscalant chemicals.